Resilience in urban civic spaces: guidelines for designing resilient social-ecological systems - Gravenstein, Gretchen (Kansas State University, 2014)
Resilience in social-ecological systems, defined by ecologist C.S. Holling (1973), is the persistence of systems after a disturbance. This theory of resilience is becoming increasingly important, especially in urban areas where human systems dominate. Therefore, creating resilient social-ecological systems is emerging as a focus for many landscape architects when designing urban landscapes. Researchers and practitioners have created frameworks and strategies for applying resilience theory, but designers are still lacking tangible methods they can use to implement design strategies to create resilient landscapes. This research presents a set of resilient design strategies, so landscape architects can have a tool to design generally resilient social-ecological systems in urban areas. In order to discover strategies which improve system resilience, I conducted a literature review and created a perceptual model of the social-ecological systems operating in the study site, Washington Square Park in Kansas City, Missouri. The perceptual model determined systems and system components I focused on in this research. These systems are soil, water, vegetation, fauna, and people. Strategies suggested by Jack Ahern (2011), Brian Walker and David Salt (2006), and Kevin Cunningham (2013) for creating resilience determined strategies which were applied to the system components in order to evaluate the park for resilience. The strategies suggested are modularity, redundancy, tight feedbacks, and ecosystem services. In addition, the system components and strategies were used to analyze case studies. I used strategies discovered in the case study analyses along with goals for the redesign of Washington Square Park, discovered by analyzing the site and previous park documents, to create the guidelines. I then used the guidelines to create a design proposal for the park. The current state of the system components in the park and the proposed state from the redesign were used to show the guidelines’ success in increasing the general resilience of Washington Square Park. These guidelines have potential to increase resilience in other urban civic spaces through a similar methodology I used for Washington Square Park. In addition, the guidelines have the potential to further research in applying resilience theory to the design of landscapes.
Keywords: Resilience theory; Resilient strategies; Site design; Landscape Architecture (0390)